Retrospective Analysis of Imaging Characteristics of Tectal Gliomas. Issue 1 (30th December 2022) - Pokhylevych, Halyna; Khose, Swapnil; Amer, Ahmad; Alhasan, Hamza; Kaya, Diana; Johnson, Rashad; Fuller, Greg; Gruschkus, Stephen K.; Zaky, Wafik; Weinberg, Jeffrey S.; Johnson, Jason M.
Abstract : Background and Purpose: Tectal gliomas (TGs) are rare tumors that involve critical locations in the brainstem, including the superior and inferior colliculi and the Sylvian aqueduct. The rarity of these tumors and the lack of large clinical studies have hindered adequate understanding of this disease. We sought to determine the association between imaging characteristics of TG and progression-free survival (PFS). Materials and Methods: In this retrospective cohort study, impact of imaging characteristics (contrast enhancement, calcifications, cystic changes, presence of hydrocephalus) on survival was analyzed for 39 patients with TG. We used the Kaplan-Meier survival analysis method for determining the association between imaging characteristics and PFS. Progression-free survival was measured from time of diagnosis to radiographic or pathological disease progression during observation period. Progression was defined as more than 25% increase of the lesion in size, per response assessment in neuro-oncology, together with clinical deterioration and/or a need for intervention. Progression-free survival differences by various imaging characteristics were assessed using the log-rank test and univariable Cox proportional hazard regression. Because most of the studies in the current literature tend to overrepresent pediatric patients, we aimed to determine the association between TG tumors' imaging characteristics and PFS in both adult and pediatric patients. All statistical analyses were performed using STATA version 16.1 (Stata Corp, College Station, Tex). Results: Of the 39 patients, radiographic tumor progression was observed in 15 cases (38.5%). Median PFS for 39 patients during observation was 21.8 years. Tectal gliomas that showed contrast enhancement initially or developed contrast enhancement during surveillance on magnetic resonance imaging had significantly lower PFS than those without (hazard ratio, 3.55; 95% confidence interval, 1.09–11.58; log-rank P value, 0.02). Conclusions: Analysis of this patient population showed that contrast-enhancing TGs should not be categorically defined as benign lesions. This subgroup of patients should be followed closely for signs of progression.